Jane - McKenna, Aline Brosh (Archaia, 2017)
"A powerful modern day reimagining of Charlotte Brontë's classic novel Jane Eyre. Jane learns that in the world of New York's elite, secrets are the greatest extravagance and she must decide if she should trust the man she loves or do whatever it takes to protect her best friend from the consequences of his deception" -- Provided by publisher.